Bad luck or bad decisions? Macroeconomic implications of persistent heterogeneity in cognitive skills and overconfidence - Oliver Pfäuti; Fabian Seyrich; Jonathan Zinman (Deutsches Institut für Wirtschaftsforschung (DIW), 2024)
Business cycle models often abstract from persistent household heterogeneity, despite its potentially significant implications for macroeconomic fluctuations and policy. We show empirically that the likelihood of being persistently financially constrained decreases with cognitive skills and increases with overconfidence thereon. Guided by this and other micro evidence, we add persistent heterogeneity in cognitive skills and overconfidence to an otherwise standard HANK model. Overconfidence proves to be the key innovation, driving households to spend instead of precautionary save and producing empirically realistic wealth distributions and hand-to-mouth shares and MPCs across the income distribution. We highlight implications for various fiscal policies.
Keywords: D91; E21; E62; E71; G51; 330; Household Heterogeneity; Cognitive Skills; Overconfidence; Financial Constraints; Fiscal Policy; HANK